Paracrossidius radekcervenkai (Coleoptera: Scarabaeidae: Aphodiinae), a new species from China - Červenka, Radek; Nakládal, Oto (Zootaxa, 2017)
A new species of Paracrossidius Balthasar, 1932 (Coleoptera Scarabaeidae: Aphodiinae) from China is described and compared with similar species. Paracrossidius was originally described as a monotypic subgenus based on the type species Aphodius (Paracrossidius) instigator Balthasar, 1932 from Sichuan Province, China. Paracrossidius is currently considered a genus with 10 previously described species, most of which inhabit various parts of China (Dellacasa et al. 2016).